2022
DOI: 10.1002/adfm.202207688
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicularly Reversed Polarization Sensitivity of Double‐faced Photodetection based on Sb2Se3 Microbelt

Abstract: Low-dimensional polarization-sensitive photodetectors have captured everincreasing attention due to their unique applications in navigation, optical switching, and communication. However, to date, the study of dimensionality-dependent polarization-sensitive photodetectors has not received much attention. Herein, a double-faced polarization-sensitive photodetector based on an individual high-quality Sb 2 Se 3 microbelt is proposed, where both the wide and narrow side facets serve as irradiation targets. Polariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 53 publications
(82 reference statements)
0
27
0
Order By: Relevance
“…According to the absorption coefficient (≈10 5 cm −1 ) for E // c , the penetration depth is calculated to be ≈100 nm. [ 50 ] It indicates that the photoinduced electrons and holes are partially excited in the depletion region, as shown in Figure 5d. The built‐in electric field in the depletion region can spatially separate carriers, significantly reducing the recombination rate, and thereby, forming a large photocurrent.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…According to the absorption coefficient (≈10 5 cm −1 ) for E // c , the penetration depth is calculated to be ≈100 nm. [ 50 ] It indicates that the photoinduced electrons and holes are partially excited in the depletion region, as shown in Figure 5d. The built‐in electric field in the depletion region can spatially separate carriers, significantly reducing the recombination rate, and thereby, forming a large photocurrent.…”
Section: Resultsmentioning
confidence: 94%
“…Due to the large thickness of Sb 2 Se 3 MB, the difference in actual absorption is small even if the absorption coefficient ( E // c ) is greatly larger than the absorption coefficient ( E // a ) in the NIR region. [ 50 ] The polarization sensitivity of the MXene/Sb 2 Se 3 MB/MXene vertical PD does not achieve the desired results.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7 summarizes the relationship between the responsivity and response time of the 250 °C-annealed selenized PDs and those of the PDs reported by other groups. [8,[38][39][40][41][42][43][44][45][46] For comparison, the key parameters (e.g., dimension, light intensity, and deposition method) that may affect the response time are given in Table S4, Supporting Information. It is noted that the proposed 250 °C-annealed selenized PDs demonstrated the highest responsivity and the fastest switching performance among the compared Sb 2 Se 3 -based devices.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…Most of the reported Sb 2 Se 3 nanostructures were synthesized using chemical vapor deposition, which is intricate and necessarily uses chemical precursors and requires high reaction temperatures, typically between 300 and 900 °C. [8][9][10] Polycrystalline Sb 2 Se 3 thin films represent an alternative avenue for conductivity enhancement. Polycrystalline Sb 2 Se 3 thin films were prepared using various methods including vapor deposition technology, thermal evaporation, chemical bath technology, and sputtering.…”
mentioning
confidence: 99%
“…In general, dimensionality engineering is an effective strategy for regulating the electronic, magnetic, piezoelectric, polarization optical, and catalytic properties. One-dimensional (1D) nanotubes, nanowires, and nanoribbons possess distinctive characteristics such as edge state, quantum scale effect, and ferromagnetism, which demonstrate their potential in serving as building blocks for spintronics, superconductivity, quantum devices, and so on. For instance, among the transition metal dichalcogenides (TMDs), it has been reported that the magnetic and electronic properties of MoS 2 nanoribbons along the zigzag direction are affected by the applied strain and external electric field in the absence of metal doping .…”
Section: Introductionmentioning
confidence: 99%